HOME-SCHOOL INTERACTION: REMODELLING A FRAMEWORK OF PARENTS-TEACHERS RELATIONSHIP FOR SUPPORTING STUDENTS’ LEARNING - Adi Suryani (JURNAL SOSIAL HUMANIORA (JSH), 2013)
Family and school are not separated social institution. Many parents view that it is schools and teachers which and who should be responsible for their children education. These views should be challenged by arising concern and awareness of parents and teachers of the importance of shared responsibility and cooperativeness. Parents are responsible for laying the basic/foundation of children’s learning, basic values, moral education, and basic social learning. Teachers and schools bear responsibility for developing those basic education. During their learning at school, students have a chance to develop their social competence. School also can be environment where children are gradually learning to be adult learners. They can be adult learners through engaging in collaborative learning activities. Through this social learning, children can learn develop social concern and sensitivity. Moreover, they can develop their learning through experience.